Impact of wind speed and soil frost on electricity distribution system reliability - Juha Haakana; Otto Räisänen; Markku Karhunen; Ilona Láng-Ritter; Jukka Lassila (Heliyon)
Wind is a significant cause of power outages in overhead line networks. Present electricity distribution network management systems provide an extensive amount of data on network faults. These data combined with the openly available weather and soil information allow to analyze the impact of wind and soil frost on electricity system reliability more accurately than in the past. The objective is to determine the effect of soil frost on wind-induced faults in the electricity distribution system and identify variables that provide the best correlation between wind speed and the number of power supply interruptions. Five geographical areas in Finland are analyzed based on extensive electricity distribution interruption statistics collected in the country between 2008 and 2018. We introduce a methodology to analyze the effect of wind speed and soil frost and present numerical data analyzed for the areas under consideration. The methodology employs a multivariate linear regression model to show the dependence between wind, soil frost, and power supply interruptions. The results indicate that there is a strong positive correlation between the number of power supply interruptions and wind speed, and furthermore, in the multivariate model, adding the variable of soil frost improves correlation in all the areas under consideration. On average, the correlation with wind gusts and the number of power supply interruptions is approximately 0.67. However, with the soil frost variable, the correlation increases to 0.72. The results show that soil frost should be considered in studies on interruption modeling in Nordic conditions.